Community-Based Education to Strengthen Landslide Risk Awareness in Gunungsari Vilage, Batu City, East Java, Indonesia - Rivandi Pranandita Putra; Vita Ayu Kusuma Dewi; Heni Masruroh; Dyah Arum Perwitasari; Diaz Heksa Bintang Pamungkas; Adip Wahyudi; Evi Fitriana; Melati Julia Rahma; Mochammad Tri Herwanto; Ferryati Masitoh; Ifan Deffinika (Institut Teknologi dan Bisnis Asia Malang, 2026)
Purpose: This study aims to enhance local capacity for landslide mitigation in Gunungsari Village, Batu City, addressing limited community awareness and unsustainable land use in landslide-prone terrain. Method: A participatory community-based education approach was implemented in July 2025, involving household visits to 50 residents across five hamlets, distribution of illustrated leaflets, and focus group discussions with hamlet leaders covering landslide triggers, early warning signs, and mitigation measures using locally-adapted visuals and language. Practical Applications: The programme offers a replicable, low-cost disaster education model for landslide-prone rural areas to improve community preparedness and engagement. Conclusion: Results demonstrated increased disaster literacy, confidence, and preparedness among residents, confirming that contextual, participatory education effectively strengthens sustainable rural disaster resilience.